Geometrical engineering of a SPAN-graphene composite cathode for practical Li-S batteries - Kim, Hun; Hwang, Jang-Yeon; Bang, Sangin; Jung, Hun-Gi; Sun, Yang-Kook (Royal Society of Chemistry, 2022)
The realization of practical lithium-sulfur (Li-S) batteries is contingent on the development of innovative electrode designs having high energy, high power and a long lifespan. Herein, we propose a compact, high-performance, 2D sulfurized-polyacrylonitrile/graphene (2D-SPAN/G) cathode for practical Li-S batteries. A 2D-SPAN/G cathode with a high active-mass (sulfur) loading of 10 mg cm(-2) is successfully prepared via high-pressure pelletization. In the 2D-SPAN/G cathode, graphene nanosheets function as a robust and conductive scaffold, which uniformly encapsulates SPAN nanoparticles, providing structural integrity and enabling the high electrochemical utilization of sulfur. The combination of the stabilized lithium metal anode, a modified electrolyte (consisting of 1 M LiPF6 and 0.05 M LiDFOB in EMC : FEC (3 : 1 (v/v))) and a 2D-SPAN/G cathode delivers a high areal capacity of 11 mA h cm(-2) and demonstrates outstanding cycling stability over 300 cycles at a high current density of 4 mA cm(-2). Moreover, the excellent electrochemical performance of a scaled-up, pouch-type Li-S battery featuring a 2D-SPAN/G cathode demonstrates the viability of the proposed cathode. The reversibility of the Li+-ion storage mechanism of the 2D-SPAN/G cathode is confirmed using operando Raman spectroscopy.